Antibacterial Peptides - Jean-Marc Sabatier (MDPI AG, 2020)
As natural host defense compounds produced by numerous prokaryotic and eukaryotic life forms, antimicrobial peptides (AMPs) are now emerging as solid candidate chemotherapeutic drugs to fight against the various types of pathogenic Gram-positive and Gram-negative bacteria, especially those resistant to current antibiotics [...]